Pemberdayaan Masyarakat Melalui Literasi Hukum dan Digital dalam Pencegahan Kekerasan Siber dan Penipuan Online di Desa Mandalle - Rismawati; Try Gustaf Said; Muh. Amar (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The Community Empowerment Program through Legal and Digital Literacy in Preventing Cyber ​​Violence and Online Fraud was implemented in Mandalle Village, West Bajeng District, Gowa Regency. This activity was motivated by the low level of legal and digital literacy of the village community which led to high vulnerability to various forms of crime in the digital space, such as cyber violence, misuse of personal data, and online fraud. This condition was triggered by the increasing use of digital technology that has not been balanced with an understanding of digital legal rights and obligations as well as available legal protection mechanisms. The purpose of this community service activity is to increase legal awareness and digital literacy skills of the community through a community empowerment approach that places citizens as the main subject in efforts to prevent cybercrime. The method of implementation of the activity is carried out through four stages, namely: (1) program socialization, (2) legal and digital literacy training, (3) mentoring and evaluation, and (4) strengthening program sustainability. The activity was carried out with a participatory approach through interactive counseling, group discussions, and direct mentoring to the community. The training phase was attended by 25 participants consisting of Family Welfare Movement (PKK) members, village officials, and community representatives who actively use digital technology in their daily lives. The results of the activity showed an increase in the community's understanding and awareness of digital law. Participants were able to identify various forms of cyberviolence and online fraud, understand reporting mechanisms and legal protection, and implement preventive measures for the safe and responsible use of digital technology. Furthermore, the active involvement of local institutions demonstrated a shift in community attitudes toward wiser and more responsible digital behavior. Thus, this community service activity was effective in strengthening the community's digital law awareness, encouraging active citizen participation, and building village social resilience in facing the challenges of cybercrime and online fraud.